Direct observation of the potential distribution within organic light emitting diodes under operation - Weigel, Christian; Kowalsky, Wolfgang; Saive, Rebecca (Physica status solidi. Rapid research letters, 2015)
We show the first direct measurement of the potential distribution within organic light emitting diodes (OLEDs) under operation and hereby confirm existing hypotheses about charge transport and accumulation in the layer stack. Using a focused ion beam to mill holes in the diodes we gain access to the cross section of the devices and explore the spatially resolved potential distribution in situ by scanning Kelvin probe microscopy under different bias conditions. In bilayer OLEDs consisting of tris(hydroxyquinolinato) aluminum (Alq3)/N, N ′-bis(naphthalene-1-yl)-N,N ′-bis(phenyl) benzidine (NPB) the potential exclusively drops across the Alq3 layer for applied bias between onset voltage and a given transition voltage. These findings are consistent with previously performed capacitance-voltage measurements. The behavior can be attributed to charge accumulation at the interface between the different organic materials. Furthermore, we show the potential distribution of devices with different cathode structures and degraded devices to identify the cathode interface as main culprit for decreased performance. (© 2015 WILEY-VCH Verlag GmbH &Co. KGaA, Weinheim)